The new US strategy towards Asia : adapting to the American pivot - Tow, William T.; Stuart, Douglas T. (New York : Routledge, 2015)
'Barack Obama's'rebalancing strategy' or'pivot strategy', intended to demonstrate continued US commitment to the Asia Pacific region in a variety of military, economic and diplomatic contexts, was launched with much fanfare in 2011. Implicit in the new strategy is a focus on China and also a US relience on existing regional allies to implement its strategy. This book explores the impact of the new strategy on the US's allies in the region, and the allies' responses. Overall, the book outlines the deep complexities of the United States' exercise of power and influence in the region'--
Setting the context / Douglas Stuart and William T. Tow -- Obama's'rebalance' in historical context / Douglas Stuart -- Rebalancing and order-building : strategy or illusion? / William T. Tow -- Deterrence, the twenty-first century, and the pivot / Jeffrey D. McCausland -- US rebalancing to the Asia-Pacific : a Japanese perspective / Ken Jimbo -- South Korea's adaptation to the US pivot to Asia / Changsu Kim -- The US pivot to Asia : Taiwan's security challenges and responses / Fu-Kuo Liu -- Strategic communication : US-Philippines relations and the American rebalancing strategy / Charmaine G. Misalucha -- A reluctant ally? : Thailand in the US rebalancing strategy / Kitti Prasirtsuk and William T. Tow -- Security and power balancing : Singapore's response to the US rebalance to Asia / Ralf Emmers -- Australia responds to America's rebalance / Brendan Taylor -- New Zealand's response / Robert Ayson -- India and the US pivot to Asia : convergence without change / Mahesh Shankar -- Balancing the risks of US rebalancing / Tongfi Kim.
Includes bibliographical references and index.
Keywords: United States -- Foreign relations -- Asia; Asia -- Foreign relations -- United States; United States -- Foreign relations -- 2009-